2003
DOI: 10.1074/jbc.m211464200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of E2A Activities by Histone Acetyltransferases in B Lymphocyte Development

Abstract: Genetic studies have demonstrated that the basic helix-loop-helix protein E2A is an essential transcription factor in B lymphocyte lineage commitment and differentiation. However, the mechanism underlying E2A-mediated transcription regulation is not fully understood. Here, we investigated the physical and genetic interactions between E2A and co-activators histone acetyltransferases (HATs) in B cells. Gel filtration analysis of human pre-B cell nuclear extract showed that E2A coelutes with the HATs p300, CBP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 33 publications
(57 reference statements)
3
70
0
3
Order By: Relevance
“…Furthermore, gel filtration analysis using HeLa nuclear extract demonstrated that SNIP1 did not coelute with p300, confirming that these two proteins do not interact in this cell line (Figure 4b). p300 was found to exist in a relatively large complex (B1 MDa) as previously reported (Bradney et al, 2003), but SNIP1 is a component of an even larger, unknown, complex. SNIP1 was not detected in any other fraction of the analysis, suggesting that all cellular SNIP1 is present in this high molecular weight complex (data not shown).…”
Section: Snip1's Effects On the Cell Cycle Are P53 Independentmentioning
confidence: 49%
“…Furthermore, gel filtration analysis using HeLa nuclear extract demonstrated that SNIP1 did not coelute with p300, confirming that these two proteins do not interact in this cell line (Figure 4b). p300 was found to exist in a relatively large complex (B1 MDa) as previously reported (Bradney et al, 2003), but SNIP1 is a component of an even larger, unknown, complex. SNIP1 was not detected in any other fraction of the analysis, suggesting that all cellular SNIP1 is present in this high molecular weight complex (data not shown).…”
Section: Snip1's Effects On the Cell Cycle Are P53 Independentmentioning
confidence: 49%
“…Moreover, few repressed target genes were highly regulated by the two E-proteins in contrast to a large proportion of the activated target genes. In support of transcriptional activation, E-proteins contain 3 activation domains (AD1, AD2, and AD3), which interact with the coactivators p300 and CBP (Bradney et al, 2003;Bayly et al, 2004) and the promoter recognition factor TFI ID (Chen et al, 2013). At the chromatin level, we identified a novel role for E-proteins in shaping the enhancer landscape at its activated target genes, as E2A and E2-2 are responsible for the induction and maintenance of DHS sites containing E2A-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Within the lymphoid system, E-proteins function as homodimers or heterodimers with a different E-protein (Bain et al, 1993;Shen and Kadesch, 1995). E-proteins are thought to mainly function as transcriptional activators, as they interact with the co-activators p300 and CBP (Bradney et al, 2003;Bayly et al, 2004), as well as the promoter recognition factor TFI ID (Chen et al, 2013). The activity of E-proteins is controlled by the inhibitor of DNA binding proteins, which are HLH proteins lacking the basic DNA-binding domain, and are thus capable of sequestering E-proteins into DNA-bindingincompetent heterodimers (Kee, 2009).…”
mentioning
confidence: 99%
“…Recent reports have also shown that coactivator p300, CBP, and PCAF enhance the E2A-mediated transcriptional activity, and promote nuclear retention of E2A proteins in 293T cells. 26 Moreover, p300 can associate with the bHLH region and the amino-terminal region of E2A proteins. 21,25 Furthermore, Deltex1 was reported to bind directly to p300, thereby counteracting p300-dependent transcriptional activation by bHLH protein.…”
Section: Notchic-activated Deltex1 Represses the Srg3 Expressionmentioning
confidence: 99%
“…21 In addition, the interaction mechanism between E2A and p300/ CBP is reported in insulin gene transcription and in pre-B cells, respectively. 26,27 E2A/HEB binding to the E-box element on SRG3 promoter regulates the SRG3 expression and, thereby, controls the sensitivity to GC-induced apoptosis in thymocytes. 18 Therefore, it is possible that Notch-induced Deltex1 may inhibit the transcriptional activity of E2A by blocking the recruitment of a coactivator(s), and this will result in reduced expression of SRG3 and resistance to the GC-induced apoptosis in developing thymocytes.…”
Section: Introductionmentioning
confidence: 99%